1997
DOI: 10.1093/protein/10.12.1465
|View full text |Cite
|
Sign up to set email alerts
|

Prion protein expression in Chinese hamster ovary cells using a glutamine synthetase selection and amplification system

Abstract: Syrian hamster prion protein (PrPC) and a truncated Syrian hamster prion protein lacking the glycosylphosphatidylinositol (GPI) anchor C-terminal signal sequence (GPI-) were expressed in Chinese hamster ovary cells using a glutamine synthetase selection and amplification system. The CHO cell clones expressing the GPI- PrP secreted the majority of the protein into the media, whereas most of the PrP produced by clones expressing the full-length protein with the GPI anchor was located on the cell surface, as demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 21 publications
4
34
0
Order By: Relevance
“…Among those, addition of the GPI anchor seems to be of particular importance. Initial experiments in cell culture revealed that a mutant devoid of the C-terminal GPI anchor signal sequence (PrP⌬GPI) is imported into the ER but remains mainly unglycosylated, spontaneously adopts a misfolded conformation and is efficiently secreted (Rogers et al, 1993;Blochberger et al, 1997;Winklhofer et al, 2003c). The phenotype of anchorless PrP described in cultured cells was recently confirmed in transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those, addition of the GPI anchor seems to be of particular importance. Initial experiments in cell culture revealed that a mutant devoid of the C-terminal GPI anchor signal sequence (PrP⌬GPI) is imported into the ER but remains mainly unglycosylated, spontaneously adopts a misfolded conformation and is efficiently secreted (Rogers et al, 1993;Blochberger et al, 1997;Winklhofer et al, 2003c). The phenotype of anchorless PrP described in cultured cells was recently confirmed in transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
“…To include a PrP conformer that misfolds in the secretory pathway, we used a mutant that contains the N-terminal ER- targeting signal but lacks the C-terminal GPI signal sequence (designated PrP⌬GPI). Targeting to and import into the ER of PrP⌬GPI is efficient, but in the secretory pathway PrP⌬GPI spontaneously adopts a misfolded conformation and is secreted (Rogers et al, 1993;Blochberger et al, 1997;Winklhofer et al, 2003c).…”
Section: Prp Directed To Different Cellular Compartments Adopts a Mismentioning
confidence: 99%
“…Chinese hamster ovary (CHO) cell lines overexpressing PrP C of the Syrian Golden hamster sequence were established by Dr. S. B. Prusiner's group (23). PrP C derived from this cell line carries both the two Nglycosylations and the C-terminally attached GPI anchor.…”
Section: Methodsmentioning
confidence: 99%
“…Our preparation is much closer to the in vivo situation than those of the earlier studies. Native PrP C , carrying the two N-glycosylations and the natural GPI anchor, purified from an eukaryotic transgenic cell line (23,24), was anchored to a solidly supported, raft-like membrane in a buffered environment. In an earlier study, we exploited the alterations of surface plasmon resonance to analyze the lipid anchoring kinetics (25).…”
mentioning
confidence: 99%
“…(40). Deletion of the C-terminal GPI anchor signal sequence prevents membrane attachment of PrP-S230X but does not interfere with import into the ER or further trafficking through the secretory pathway (24,27,41). PrP-S230X is secreted both by cultured cells (Fig.…”
Section: Protein Hydrophobicity Plot-mentioning
confidence: 99%